No causal association between pneumoconiosis and three inflammatory immune diseases: a Mendelian randomization study - Du, Yu-Jie; Lu, Zhang-Wei; Li, Kai-Di; Wang, Yi-Yu; Wu, Hong; Huang, Rong-Gui; Jin, Xue; Wang, Yi-Yuan; Wang, Jing; Geng, An-Yi; Li, Bao-Zhu (Frontiers in Public Health, 2024)
Objectives. To investigate the causal relationships between pneumoconiosis and rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and gout. Methods. The random-effects inverse variance weighted (IVW) approach was utilized to explore the causal effects of the instrumental variables (IVs). Sensitivity analyses using the MR-Egger and weighted median (WM) methods were did to investigate horizontal pleiotropy. A leave-one-out analysis was used to avoid the bias resulting from single-nucleotide polymorphisms (SNPs). Results. There was no causal association between pneumoconiosis and SLE, RA or gout in the European population [OR = 1.01, 95% CI: 0.94-1.10, p = 0.74; OR = 1.00, 95% CI: 0.999-1.000, p = 0.50; OR = 1.00, 95% CI: 1.000-1.001, p = 0.55]. Causal relationships were also not found in pneumoconiosis due to asbestos and other mineral fibers and SLE, RA and gout [OR = 1.01, 95% CI: 0.96-1.07, p = 0.66; OR = 1.00, 95% CI: 1.00-1.00, p = 0.68; OR = 1.00, 95% CI: 1.00-1.00, p = 0.20]. Conclusion. Our study suggests that pneumoconiosis may have no causal relationship with the three inflammatory immune diseases.